Plant typology in urban development as a natural barrier protecting citizens from external natural factors - Kozak, Alevtyna (КНУБА, 2025)
Green spaces in urban areas not only create an aesthetic appearance, but also play a functional role in protecting people from noise, wind, dust and overheating. They can be called the lungs of cities. The article examines the typology of plants in urban areas from the point of view of their impact on the microclimatic conditions of the city's inhabitants.
Keywords: typology of plants in urban development; dust protection; noise protection; wind protection